Analisis Kepatuhan Wajib Pajak dalam Membayar Pajak Restoran Studi Kasus pada Badan Pengelola Pajak dan Retribusi Daerah Kabupaten Musi Rawas - Yayuk Marliza; Miki Indika; Apriani Apriani (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2020)
The purpose of this study is to know the compliance of taxpayer to pay the restaurant tax. This study is conducted in the tax management and retributions Body of Musi Rawas Regency. The data is collected during 2016 -2018 . This research used deskriptive and qualitative and the data used are primery data abd secondary data. Methods of data collection interviews,observation and documentations. There is one variable, namely tax payer compliance . the restuls of the analysis show that restaurant taxpayer compliance is categorized to be obdient, it can be seen annual submitting the regional tax notice. (SPTPD), having no tax arrears for ail tipes oftax having obtainted permissions to pay in installments and delaying tax payments, never sentenced texations in the past ten years.